In Defence of 'Noir Theory': Laruelle, Deleuze, and Other Detectives. (May 2020) - Coley, Rob
What happens when theory falters? A concern with the anthropocentric limitations of critical thought dominates contemporary cultural theory. For Joanna Zylinska, however, this concern often reflects a longstanding humanist anxiety, one that is today renewed in the form of 'noir theory', a reactionary scholarship that redeems the universalist human as the subject of reason. There is, though, more than one mode of noir theory, and a certain tendency of 'noir' affords the basis for theorizing another kind of universalism, a non-reactionary account of the real. This article takes seriously the allusion to noir as a particular mode of detection. Its investigation begins with Gilles Deleuze, who commends crime fiction for providing an image of thought that works against humanist orthodoxy. Yet present circumstances demand investigating a blacker kind of noir, one that operates negatively, a noir theory that can be detected in the strange realism of François Laruelle.